Revitalizing the Livelihoods of Kahayan River Communities: Exploring the Determinants of Income Increase - Andrie Elia; Basrowi Basrowi (Shirkah: Journal of Economics and Business, 2023)
Identifying strategies for increasing the income of densely populated communities, particularly concerning the COVID-19 pandemic, remains a challenge. Specifically, this study aims to investigate the influence of entrepreneurial interest, digital marketing, and financial capital on income generation in Pahandut Village. The study adopts a quantitative research methodology based on a sociological-economic approach. Data analysis involves the use of multiple linear regression analysis. A random sampling technique was utilized to select 152 respondents from the entire population of Pahandut village. The findings reveal that entrepreneurial interest, digital marketing, and financial capital have a positive and significant influence on income generation during the Covid-19 pandemic. Therefore, it can be concluded that greater entrepreneurial interest, utilization of digital marketing, and financial capital will increase income for Kahayan River bank community during the Covid-19 pandemic era. Therefore, to adapt to the evolving business landscape, it is crucial to provide support for business literacy aimed at both starting and expanding a business.